Experiences of Visible Minority Librarians and Students in Canada from the ViMLoC Mentorship Program - Li, Yanli; Ly, Valentina; Li, Xuemei (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2023)
Objective – The purpose of this research is to examine the experiences of mentors and mentees in the formal mentorship program offered by the Visible Minority Librarians of Canada Network (ViMLoC) from 2018-2022. Findings from this research will help mentors and mentees understand how to establish an effective mentoring relationship. Professional library associations and libraries can also gain valuable insights to support the visible minority library professionals within their own mentorship programs.Methods – Between 2018 and 2022, 113 mentors and 145 mentees participated in four sessions of the ViMLoC mentorship program. The ViMLoC Mentorship Committee designed and delivered a survey for mentors and a survey for mentees at the end of each session. Over four sessions, 81 mentors and 82 mentees completed the surveys, representing a 72% and 57% completion rate, respectively. Fisher's Exact Tests were performed to examine if there were significant differences between mentors and mentees in their perceptions regarding ease of communication, relationship, helpfulness of mentorship, likeliness of keeping in contact, and importance of having a visible minority partner.Results – The mentees perceived mentoring support to be more helpful than the mentors perceived it themselves. The mentees were more likely to keep in contact with their mentors beyond the mentorship program while the mentors did not show as much interest. The mentees who had a positive experience from the formal mentorship program were found to be more likely to mentor others in the future, whereas the same effect did not hold true for the mentors. On the other hand, some findings were the same for both mentors and mentees. Both stated that effective communication would facilitate a good mentoring relationship, which in turn, would lead to positive outcomes and greater likelihood of keeping in contact beyond the mentoring program. There was also consensus of opinion about the most important areas of mentoring support and some essential skills for building a successful mentoring relationship.Conclusion – This research contributes to the literature by using an empirical research method and comparative analyses of the experiences between mentors and mentees over four sessions of the ViMLoC mentorship program. The study focuses on the perceptions of participants regarding their communication, relationship, helpfulness of mentorship, associations between their past and present mentoring experiences, areas of support, importance of having a visible minority partner, and essential skills for building a successful mentoring relationship. Mentors and mentees differed significantly in how they perceived the helpfulness of mentorship support and how likely they would like to maintain the ties beyond the program. For both sides, effective and easy communication was found to be critical for building a good mentoring relationship and achieving a satisfactory experience.